The Incidence of Ectopic Pregnancy and its Diagnostic Accuracy by Clinical, Ultrasound and Intraoperative Findings (Nepalese Journal of Radiology, 2022)
Introduction: In an ectopic pregnancy, most patients present with 5 to 9 weeks of amenorrhea, mild pelvic pain and vaginal spotting which triggers the evaluation of ectopic pregnancy. The presence of an extrauterine gestational sac containing a yolk sac or embryo is the most specific sonographic finding whereas an echogenic tubal ring in the adnexa is the most common finding.1  This study aimed to find the accuracy of ultrasound findings versus clinical presentation, intraoperative findings and histological findings.Methods: This is a retrospective study. All patients with histopathological diagnoses of ectopic pregnancy were included in the study and data regarding clinical diagnosis, ultrasound diagnosis and intraoperative diagnosis were retrieved and compared with their histopathological diagnosis.Result: There were 216 cases of ectopic pregnancy with an overall incidence of ectopic pregnancy was 0.88%. The sensitivity with ultrasound diagnosis was 99.52% and specificity 11.11% with positive and negative predictive values were 96.2 % and 50 % respectively and overall diagnostic accuracy of 95.83%. The sensitivity was 97.6% and specificity was 11.1% for clinical diagnosis of ectopic pregnancy. The sensitivity was 100% for intraoperative diagnosis of ectopic pregnancy with a positive predictive value is 95.83%.Conclusion: Clinical diagnosis, intraoperative findings and ultrasound findings were highly sensitive to detecting ectopic pregnancy in the study population. The overall diagnostic accuracy was highest for the ultrasound finding.